Finding Harmony in the Digital Age : Integrating Spiritual Values for Balance - Lidiawati Lidiawati (Philosophy Global: International Journal of Christian and Catholic Philosophy, 2025)
Advances in digital technology have changed the way of living and interacting in modern society. Although it provides many conveniences, technology also has the potential to disrupt the balance of life and cause alienation from the spiritual dimension. This research explores multidisciplinary approaches that can be applied to integrate spiritual values into digital lifestyles holistically and contextually. Through a literature review, several main approaches can be identified, namely digital theology, digital psychology, digital sociology, technology ethics, and integrative multidisciplinary approaches. The digital theology approach emphasizes the importance of presenting spirituality in a format relevant to the digital generation. Digital psychology examines the impact of technology on mental health and offers spiritual activity as a solution. Digital sociology looks at changes in community structure and opportunities for building virtual spiritual communities. Technology ethics considers the moral and spiritual implications of technological development. Lastly, an integrative multidisciplinary approach combines multiple perspectives to offer a comprehensive solution. By combining these approaches, this study seeks to find a balance between advances in digital technology and the appreciation of spiritual values in an online-connected society.